Update 2017 on Target Fabrication Requirements for High-Performance NIF Implosion Experiments. (17th February 2018) - Haan, S. W.; Clark, D. S.; Weber, C. R.; Baxamusa, S. H.; Biener, J.; Berzak Hopkins, L.; Bunn, T.; Callahan, D. A.; Carlson, L.; Edwards, M. J.; Hammel, B. A.; Hamza, A.; et al.
Abstract: Experiments and analysis in the 2 years since the 2015 Target Fabrication Meeting have resulted in further evolution of the requirements for high-performance layered implosions. This paper is a status update on the experimental program and supporting modeling, with emphasis on the implications for fabrication requirements. Previous work on the capsule support has continued, with various other support options being explored in experiments and modeling. Work also continues on ablator composition nonuniformities, with important new results from CH experiments on Omega, and the first three-dimensional X-ray transmission measurements of Be capsules on the National Ignition Facility. Work on hohlraums continues to include near-vacuum hohlraums and U hohlraums without a gold lining. Overall, the understanding that has been achieved, along with the progress in fabrication technology, represents good continuing progress toward the goal of fusion in the laboratory.